Interaction between C₆₀ and gases under pressure - Sundqvist, B. (Физика низких температур, 2003)
A brief review is given of the interaction between fullerite C₆₀ and various gases under elevated pressure. Subjects discussed include the formation of ordered interstitial gas-fullerene compounds, reactions between intercalated gases and fullerene molecules to form new endohedral and exohedral compounds, and changes in the structure and properties of C₆₀ because of intercalated gas atoms or molecules.